The Mediating Role of Hard Quality Management in the Relationship Between Soft Quality Management and Innovation Performance - Ehsan Masoudi (SEISENSE Journal of Management, 2024)
Purpose - Hard and soft quality management are known as two important dimensions of total quality management (TQM) that can improve the performance of manufacturing and service organizations. The paper aims to examine the effect of soft quality management (soft QM) on innovation performance (IP) with the mediating role of hard quality management (hard QM). Design/Methodology - A questionnaire was designed for the model test and distributed among 130 small and medium-sized enterprises (SMEs) in Golpayegan industrial town located in Iran. PLS-SEM was used to analyze the data.Findings - The results showed that soft QM affects hard QM and IP. Also, the impact of hard QM on IP was confirmed. The mediating role of hard QM in the relationship between soft QM and IP was also confirmed.Practical Implications - The findings of this research encourage managers of SMEs to focus attention on hard and soft QM simultaneously to improve innovation performance in companies.